2015
DOI: 10.1021/acs.jchemed.5b00512
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the Traditional Graduate Chemistry Literature Seminar with a Chemical Research Literacy Course

Abstract: The new course, CH584Literature and Communication in Graduate Chemistry, replaced a second year graduate student literature seminar requirement. Course topics included chemical information resources, critical analysis, scientific writing, scientific presentations, and peer-review. CH584 was well received by both the chemistry faculty and chemistry graduate students. This article discusses the detailed implementation and content taught in CH584. Moreover, we present our experiences teaching CH584 as well as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…4 On the other hand, instruction that is too cursory can lead to student understanding that is simplistic, passive, or shallow. 15 An important consideration for any form of teaching is the students' ability to retain information over time. Despite the importance of information literacy in undergraduate education, studies regarding the lasting effects of instruction in the subject are uncommon.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4 On the other hand, instruction that is too cursory can lead to student understanding that is simplistic, passive, or shallow. 15 An important consideration for any form of teaching is the students' ability to retain information over time. Despite the importance of information literacy in undergraduate education, studies regarding the lasting effects of instruction in the subject are uncommon.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fourth, with respect to discoverability, in recent years several articles have shown that training in these products has led to improved quantity and quality of their usage, and the question that arises, as a result of the understanding of the similarities and differences between Reaxys and SciFinder presented in this article, relates to what current teaching may need to change. A major difference that needs to be taught relates to searching by text terms, and most specifically relating to the text search functions of Search Reaxys (where the actual searches are displayable through the function called Edit in Query Builder) and Explore by Research Topic (where the actual searches are not displayable).…”
Section: Search Comparisonsmentioning
confidence: 95%
“…Most of the recommendations that are focused on the mentoring and training of graduate students were identified as high priorities by all stakeholder groups and include providing greater oversight over the progress and opportunities of individual graduate students (Figure S2), active diagnosis and remediation of deficiencies in the preparation of first-year students (especially strongly supported by first-year students and faculty, Figures and S3), incorporation of additional professional skills into graduate curricula (albeit less supported by faculty, Figures and S4 and vide infra), and the use of Individual Development Plans (IDPs) in the graduate-student-mentoring process (particularly supported by administrators, Figure S7). …”
Section: Consensus High-priority Issuesmentioning
confidence: 99%